2018
DOI: 10.1007/s13205-018-1302-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of myo-inositol hexakisphosphate (IP6): specificity, kinetics, and simulation

Abstract: Microbial degradation of -inositol hexakisphosphate (IP6) is crucial to deal with nutritional problems in monogastric animals as well as to prevent environmental phosphate pollution. The present study deals with the degradation of IP6 by microorganisms such as spp. and. These microbes were screened for phytase production under laboratory conditions. The specificity of the enzyme was tested for various phosphorylated substrates such as sodium phytate (IP6), sodium hexametaphosphate, phenyl phosphate, α-d-glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
3
2
0
Order By: Relevance
“…Phytate induced the production of extracellular phytase within 24 h of incubation in the present study. A similar result was obtained for other bacterial phytases reported in Priyodip and Balaji ( 2018 ). However, most of the bacterial phytase activities reported to date were observed after a longer incubation.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Phytate induced the production of extracellular phytase within 24 h of incubation in the present study. A similar result was obtained for other bacterial phytases reported in Priyodip and Balaji ( 2018 ). However, most of the bacterial phytase activities reported to date were observed after a longer incubation.…”
Section: Resultssupporting
confidence: 90%
“…This was proved by the lowest Michaelis-Menten constant (K m ) value of 299.50 ± 4.95 μM in comparison with 320.54 ± 12.03 μM obtained for sodium hexametaphosphate, 2011.89 ± 123.85 μM for phenyl phosphate, 875.19 ± 82.77 μM for α-D-glucose-6 phosphate, 343.02±10.06 μM for Inosine 5′ monophosphate, and 1124.39 ± 77.01 μM for pyridoxal 5′ phosphate. Similar phytate-specific bacterial phytases were reported for Bacillus subtilis with K m 293 μM (Jain et al 2018 ), Sporosarcina globispora with K m 254.90 ± 8.52 μM (Priyodip and Balaji 2018 ), Bacillus amyloliquefaciens with K m 550 μM (Kim et al 1998 ), Bacillus spp. with K m 50 μM (Choi et al 2001 ), and Escherichia coli with K m 130 μM (Greiner et al 1993 ), respectively.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Sumengen et al (109) reported high intra-and extra-cellular phytase activity for L. plantarum. A high phytase activity was also reported for S. thermophilus by Priyodip and Balaji (110,111). However, in the present study, no significant differences were observed between the strains, which could suggest the similar activity of phytase among ST and LP.…”
Section: Phytic Acidsupporting
confidence: 60%
“…Recent studies showed that phytate degradation by recombinant probiotic LAB could provide a solution for phosphate utilization in humans (254, 255). Regarding this topic, Vasudevan et al (247) reviewed the contributions of recombinant technology to phytase research during the last decade with specific emphasis on new generation phytases.…”
Section: Fermentationmentioning
confidence: 99%